Bone tunnel enlargement after the reconstruction of anterior cruciate ligament using bone-tendon-bone graft - Ninković, Srđan; Harhaji, Vladimir; Rašović, Predrag; Gvozdenović, Nemanja; Obradović, Mirko (Vojnosanitetski pregled, 2020)
Abstract Background/Aim. Bone-tendon-bone (BTB) graft is one of the strongest biological grafts and it provides a strong initial fixation with the application of interference screws making possible the primary bone healing and bone integration of the graft on the place of fixation during arthroscopic reconstruction of the arterior cruciate ligament of the knee. The aim of our research was to determine if BTB graft from which, throughout the surgical treatment, soft tissue and periosteum are removed, leads to the reduction of the enlargement in the femoral and tibial bone after the arthroscopic reconstruction of the anterior cruciate ligament. Methods. The first phase consisted of bio-mechanical study on 12 pairs of cadaveric BTB grafts. The testing was performed on the mechanical testing machine. The second phase involved clinical testing. The first group consisted of 40 patients treated with the classical BTB autograft. The second group consisted of 56 patients who had two thirds of the bony parts of the bone-tendon-bone autografts of the soft tissue and periosteum removed. We measured the distance between the edge of the sclerotic tunnel on the tibial and femoral bone in three different points: proximal (F1;T1), middle (F2;T2) and the lower part (F3;T3). Results. The experimental part of the study showed no statistically significant difference in graft breakout force expressed in N/mm2 between classically treated BTB graft and graft with a partially removed soft tissue and periosteum. By comparing the expansion of tunnels in all segments in both bone tunnels between study groups, statistically significantly lower enlargement was measured in the group with BTB grafts with partially removed soft tissues and periosteum (p < 0.05). Conclusion. The use of BTB grafts with partially removed soft tissues and periosteum provides less bone tunnel expansion as compared to classically treated grafts of the anterior cruciate tendon.